2021
DOI: 10.1142/s2424862221500020
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Industry 4.0 Implementation Barriers in Indian SMEs

Abstract: Production in small and medium enterprises (SMEs) makes a substantial contribution to the Gross Domestic Product directly and indirectly in developing economies including India. In the present time, applying Industry 4.0 to the SMEs will build a smart manufacturing system that will prove to be economically feasible as well as socially sustainable. The purpose of this study is to identify and prioritize major barriers of implementing Industry 4.0 in Indian SMEs. A questionnaire with 12 barriers which were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Adicionalmente, el uso y aplicación de las tecnologías digitales de la Industria 4.0, permite a las compañías textiles tener una visibilidad y un control más eficiente de su cadena de suministro, maquinaria e instalaciones mediante la integración de almacenes, operaciones industriales y optimización de procesos productivos, comúnmente llamados empresas inteligentes (Ghobakhloo, 2018;Leos et al, 2018;Tseng et al, 2018;Ceipek et al, 2021;Usai et al, 2021). Así, por ejemplo, la implementación del internet de las cosas permite a las compañías textiles mejorar sus sistemas de gestión de los cambios en la formación de valores de la ingeniería tales como el uso de tecnología convencional, ciclos de innovación, incremento en la visibilidad del mercado y una atmósfera de negocio extremadamente dinámica en la presión internacional por lograr mejores niveles de competitividad (D'Ippolito et al, 2019;Ceipek et al, 2021;Kumar et al, 2022).…”
Section: Implementación De La Industria 40 En La Industria Textil En ...unclassified
“…Adicionalmente, el uso y aplicación de las tecnologías digitales de la Industria 4.0, permite a las compañías textiles tener una visibilidad y un control más eficiente de su cadena de suministro, maquinaria e instalaciones mediante la integración de almacenes, operaciones industriales y optimización de procesos productivos, comúnmente llamados empresas inteligentes (Ghobakhloo, 2018;Leos et al, 2018;Tseng et al, 2018;Ceipek et al, 2021;Usai et al, 2021). Así, por ejemplo, la implementación del internet de las cosas permite a las compañías textiles mejorar sus sistemas de gestión de los cambios en la formación de valores de la ingeniería tales como el uso de tecnología convencional, ciclos de innovación, incremento en la visibilidad del mercado y una atmósfera de negocio extremadamente dinámica en la presión internacional por lograr mejores niveles de competitividad (D'Ippolito et al, 2019;Ceipek et al, 2021;Kumar et al, 2022).…”
Section: Implementación De La Industria 40 En La Industria Textil En ...unclassified
“…The application of Internet of Things (IoT) technologies can manage the challenges in engineering value formation, such as smaller technology and invention cycles, increasing marketplace unpredictability, and an extremely dynamic atmosphere in the aspect of snowballing competitive pressure (Ceipek et al, 2021;D'Ippolito et al, 2019;Kumar et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…India has a strong focus on manufacturing and has taken new initiatives such as the "Make in India" program to accelerate manufacturing in the country and increase the share of manufacturing in GDP to 25 % (Kamble et al, 2018). India's industrial policy aims to make the country a leader in the usage and implementation of Industry 4.0 (Liao et al, 2017;Srivastava et al, 2022;Kamble et al, 2018;Kumar et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The study [21] revealed that the major implementation barriers of DTE in Indian SMEs are fear of unemployment and lack of IT training. Resistance [11] may come from employees, who are satisfied with the existing systems [19] and are fearful of their jobs ENVIRONMENTAL DYNAMISM [4].…”
Section: Challenges Opportunities and Dte Implementationmentioning
confidence: 99%